DEVELOPMENT AND PHYSICAL CHARACTERIZATION OF A PERIODONTAL BIOADHESIVE GEL OF GATIFLOXACIN - Kassab, Hanan Jalal; Thomas, Lena Murad; Jabir, Saba Abdulhadi (International Journal of Applied Pharmaceutics, 2017)
Objective: The aim of this study was to develop a bioadhesive gel of gatifloxacin for the treatment of periodontal diseases. Methods: Periodontal gels of gatifloxacin were prepared using different hydrophilic polymers such as carbopol 940 (CP 940), carboxymethyl cellulose (CMC) and hydroxypropylmethyl cellulose (HPMC) in varied concentrations, either alone or as a combination. The prepared gels were evaluated for their physical appearance, pH, drug content, viscosity, bioadhesiveness and in vitro drug release profile. The influence of the type and the concentration of polymer on the drug release as well as on viscosity and mucoadhesiveness of prepared gels were investigated. Results: The prepared gels showed acceptable physical properties concerning color, homogeneity, consistency, spreadability, and pH value. Using different polymer types at different concentrations, as well as different polymer combinations, play a significant role in the variation of overall characteristics of formulations. Increasing the concentration of polymer increased the viscosity as well as mucoadhesion, and reduced drug release rate. Formulation F 11 (1 % CP 940 and 5 % CMC) was selected as the formula of choice based on the data of various evaluation parameters such as pH, drug content, viscosity, spreadability and bioadhesion as well as its ability to show a prolonged drug release pattern. Conclusion: The obtained results show that a bioadhesive periodontal gel of gatifloxacin can be prepared using hydrophilic polymers, and by using a combination of polymers the viscosity, mucoadhesiveness, spreadability and release behavior can be optimized.